"Gastric cytoprotection" is still relevant. (December 2014) - Szabo, Sandor
Abstract: Although Andre Robert's historic article on "gastric cytoprotection" in 1979 introduced this new name and concept, gastroprotective drugs (e.g. sofalcone, sucralfate), which prevent and/or accelerate healing of gastric ulcers without inhibiting acid secretion, were known in Japan before or around that time. But since Robert's studies were solely focused on prostaglandins (PG), they became the center of gastrointestinal research for more than 30 years. As endogenous products, PG were implicated in mediating the gastroprotective effect of other drugs such as sofalcone and sucralfate, despite that the cyclooxygenase inhibitor indomethacin diminished but never abolished gastroprotection by other drugs. Another group of endogenous substances, that is, sulfhydryls (SH), investigated in parallel with PG, also seem to play a mechanistic role in gastroprotection, especially since SH alkylators like N‐ethylmaleimide counteract virtually any form of gastroprotection. In Robert's terms of "prevention of chemically induced acute mucosal lesions, " so far no single mechanism could explain the beneficial effects of diverse protective agents, but I argue that these two endogenous substances (i.e. PG, SH), in addition to histamine, are the main mechanistic mediators of acute gastroprotection: PG and histamine, because as mediators of acute inflammation, they increase vascular permeability (VP), and SH scavenge free radicals. This is contrary to the search for a single mechanism of action, long focused on enhanced secretion of mucus and/or bicarbonate that may contribute but cannot explain all forms of gastroprotection. Nevertheless, based on research work of the last 30 years, in part from our lab, a new mechanistic explanation of gastroprotection may be formulated: it's a complex but orderly and evolution‐based physiologic response of the gastric mucosa under pathologic conditions. Namely, one of the first physiologic defense responses of any organ is inflammation that starts with rapid vascular changes (e.g. increased VP and blood flow), followed by cellular events (e.g. infiltration by acute and chronic inflammatory cells). Thus, PG and histamine, by increasing VP create a perivascular edema that dilutes and delays toxic agents reaching the subepithelial capillaries. Otherwise, damaging chemicals may induce severe early vascular injury resulting in blood flow stasis, hypoxia, and necrosis of surrounding epithelial and mesenchymal cells. In this complex response, increased mucus and/or bicarbonate secretion seem to cause luminal dilution of gastrotoxic chemicals that is further reinforced by a perivascular, histodilutional component. This mechanistic explanation would encompass the protective actions of diverse agents as PG, small doses of histamine, motility stimulants, and dilute irritants (i.e. "adaptive cytoprotection"). Thus, although markedly increased VP is pathologic, slight increase in VP seems to be protective, that is, a key element in the complex pathophysiologic response during acute gastroprotection. Over the years, "gastroprotection" was also applied to accelerated healing of chronic gastroduodenal ulcers without reduction of acid secretion. The likely main mechanism here is the binding of angiogenic growth factors (e.g. basic fibroblast growth factor, vascular endothelial growth factor) to the heparin‐like structures of sucralfate and sofalcone. Thus, despite intensive research of the last 30 years, gastroprotection is incompletely understood, and we are still far away from effectively treating Helicobacter pylori ‐negative ulcers and preventing nonsteroidal anti‐inflammatory drugs‐caused erosions and ulcers in the upper and lower gastrointestinal tract; hence "gastric cytoprotection" research is still relevant.